The mediating effect of social adaptation and the moderating effect of prosocial behavior on the relationship between physical activity and psychological capital - Qiang Xue; Tianci Wang; Yuyang Nie; Xishuai Wang; Xiansen Yao; Jiyun Zhang; Yanyue Li; Han Sun; Cong Liu; Jinchao Gao (Scientific Reports)
Abstract This study aims to explore the relationship between physical activity, social adaptation, pro-social behavior, and psychological capital, and to examine the mediating role of social adaptation in the influence of physical activity on psychological capital and the moderating role of pro-social behavior on this mediating effect. In this study, a cross-sectional study design was used to conduct a questionnaire survey on 415 students from a 211 university in Ningxia, and their physical activity, psychological capital, social adaptation and prosocial data were collected during the break. In addition, this study conducted Harman single factor test, independent sample t test, descriptive statistics, correlation analysis, and moderated mediating effect model analysis on the data. Physical activity was positively correlated with psychological capital, social adaptation and prosocial behavior. Social adaptation plays a mediating role in the influence of physical activity on psychological capital, and prosocial behavior has a moderating effect on this mediating process ( the moderating effect value is – 0.018 ). When prosocial behavior is at a low level, there is significant mediation of physical activity on psychological capital through social adaptation, but when prosocial behavior is a high level, mediation is not significant. Physical exercise helps to improve the psychological capital of college students, and social adaptation plays an intermediary role in this process; at the same time, it should be noted that prosocial behavior has a moderating effect on the mediating process. This suggests that we should fully consider the impact of prosocial behavior when formulating relevant interventions.